Pemphigus Vulgaris: Application of Occlusal Soft Splint with Topical Steroid in the Treatment - G Vivekanandh Reddy; G Ramlal; K Jitendar Reddy; K Swetha; A Madhavi (Wolters Kluwer Medknow Publications, 2011)
Pemphigus vulgaris (PV) is a rare autoimmune bullous dermatosis with a high mortality rate if untreated. It is characterized by the binding of IgG autoantibodies to desmogleins 3 (DSG 3), a transmembrane glycoprotein adhesion molecule present on desmosomes. This glycoprotein strengthens the intercellular connection, and loss of this connection due to the antigen-antibody reaction weakens and finally breaks the connection between epithelial cells resulting in blisters and desquamation Patients with PV mainly involving the mucosa have antibodies directed against DSG 3, but patients with PV involving both the skin and mucosa will have antibodies against both DSG 3 and DSG 1. Most patients are initially misdiagnosed and improperly treated for many months or even years. Dental professionals must be sufficiently familiar with the clinical manifestations of PV to ensure early diagnosis and treatment, since this in turn determines the prognosis and course of the disease.